Comprehension of Labrador Inuttitut Functional Morphology by Receptive Bilinguals - Sherkina-Lieber, Marina
This study examines knowledge of grammar by receptive bilinguals (RBs) - heritage speakers who describe themselves as capable of fluent comprehension in Labrador Inuttitut (an endangered dialect of Inuktitut), but of little or no speech production in it. Despite the growing research on incomplete acquisition, RBs have yet to be studied as a specific population. Participants (8 fluent bilinguals, 17 RBs, 3 low-proficiency RBs) performed a morpheme comprehension task and a grammaticality judgment task. General measures of their comprehension and production abilities included a story retelling task as an overall assessment of comprehension, a vocabulary test, an elicited imitation task, and a production task. This data was complemented by language behaviour interviews. The results showed that RBs have good, though not perfect, comprehension and basic vocabulary, but speech production is very difficult for them. They have grammatical knowledge, but it is incomplete: Knowledge of some structures is robust, and their comprehension is fluent (past vs. future contrast, aspectual morphemes); others are missing (temporal remoteness degrees); and yet for others (case and agreement), RBs have the category and know its position in the word structure, but have difficulty connecting the features with the morphemes expressing them. These findings explain the significant asymmetry between comprehension and production in RBs: In comprehension, incomplete knowledge may result in loss of some aspects of meaning, but in many cases it can be compensated for by pragmatic knowledge and extralinguistic context, while in production, it can result in the selection of an incorrect morpheme or inability to select a morpheme. Low-proficiency RBs have partial comprehension, small vocabulary, and almost no production. They do not understand most functional morphemes; however, they show knowledge of the basic properties such as the position of the obligatory agreement marker on the verb. This study provides data on an understudied language and an understudied population at the extreme end of unbalanced bilingualism. The findings have implications both for the psycholinguistics of bilingualism and for language revitalization, especially in the context of a language shift in indigenous language communities, where RBs are often the last generation to have competence in the indigenous language. PhD